PENDAMPINGAN DAN WORKSHOP PENULISAN ARTIKEL PENELITIAN TINDAKAN KELAS BAGI GURU MGMP BAHASA JEPANG JOMBANG - Indrowaty, Sri Aju -; Puspitasari, Dewi; Indah Lestari, Eka Marthanti (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract : The low productivity of teachers in writing scientific papers has become the subject of discussion conducted by the Community Service Team with representatives of the Japanese MGMP teacher in the city of Jombang. There are many factors behind the low teacher publications. Therefore, the Team tried to help increase the number of teacher publications by conducting seminars on classroom action research and followed up with workshops on writing scientific papers. After the workshop activities, a certificate with the conversion of hours (JP) will be given so that it can be used by teachers of Japanese language MGMP members for promotion. Scientific papers that have been written will be reviewed and provided with feedback so that later the article is appropriate and will be directed to be submitted to certain journals in accordance with classroom action research. Keyword: Journal articles; Classroom action research; Japanese language teacher